Analisa Dampak Penambahan Line Flushing Injeksi Phosphate - Arief Suardi Nur Chairat; Moch Zainal Arifin (JURNAL POWERPLANT, 2014)
Condensate water is the main ingredient in the process of generating steam in the power plant condensate water uap. Therefore must have a good quality so it does not cause damage to the equipment - equipment such as pipes, tubes, valves and others. To produce water quality condensate desirable it is necessary chemicals include phosphate, ammonia and chemical hydrasin. Material is injected into some equipment such as deaerator, steam drums and others. On this occasion the discussion is about the injection of chemicals phospat. Material the chemicals injected into the water condensate (feed water) which will be precisely in the boiler to the steam injection process takes drum. For pump chemicals from the tank in order to get to the steam drum. Therefore the pump and the output pipe leading the steam drum to be reliable so it does not interfere with the injection process resulting in the boiler water quality does not match the prescribed standards that disrupts the production of listrik.Namun on the way there has been a disruption especially at pipe outlet (discharge line) to the steam drum is clogged (plugging) .This occurs because after the injection process there are still remaining - the rest of phosphate in the pump, pipe valve outlet and then dries and crystallizes as kapur.This happens especially when the power is turned off for a long time (over houl). From the above problems it is necessary to add the channel for flushing (flushing) on ​​the pump and the discharge channel leading to the steam drum, especially when the power will be off for a long time so there is no plugging in the pipe leading to the pump outlet steam line drum. The addition of the plumbing connected condensate (from discharge CEP) to the pump inlet pipe phosphate.